(untitled) (Linguamática, 2018)
Natural Language Processing (NLP) techniques are often used to enrich applications in several areas. Tools that implement or support the development of these techniques can be complex to maintain and exploit, and specific domain knowledge is usually required. This paper introduces the PLN.PT, an online platform that enables a set of tools for natural language processing as a web-service (REST API), mainly focused on the portuguese language.